THE EFFECT OF SELF EFFICACY ON MATHEMATICAL PROBLEM-SOLVING ABILITY BASED ON NEWMAN'S STAGES - Luthfi Hanafiah Alhaidar; Hanifah Hanifah; Muthiah Fildzah Noverli (JME (Journal of Mathematics Education), 2026)
Students' low ability to solve contextual mathematical problems is often influenced by affective factors, one of which is self-efficacy. This study aims to determine the effect of self-efficacy on students' mathematical problem-solving ability based on Newman's stages. The research approach used was quantitative with a causal-associative method. The sample in this study consisted of 31 students. The research instruments consisted of a self-efficacy questionnaire and a mathematical problem solving ability test. Data analysis techniques included prerequisite tests and hypothesis testing using the t-test and the coefficient of determination. The analysis results showed a significant value of 0.010 0.05, so it can be concluded that there is a significant influence of self-efficacy on students' mathematical problem-solving ability, namely 20.7%.